MINAT PERILAKU PENGGUNAAN YOUTUBE SEBAGAI SUMBER PEMBELAJARAN DENGAN PENDEKATAN TAM - Nastiti Pertiwi; Osa Omar Sharif (Faculty of Economic and Business, University of Pasundan, 2019)
This study aims to determine factors that influence the use of information resources from Youtube for learning purposes. This study is TAM model to identify behavioral intention of Youtube as a learning resource. It aims to know the effects of Perceived Ease of Use towards Perceived Usefulness, Perceived Ease of Use towards Attitude to Use, Perceived Usefulness towards Attitude to Use, and Attitude towards Use towards Behavioral Intention. Also, to know whether this model fits to the studied data. Samples comes from 155 respondents. This research uses Sctructural Equation Modelling. The result of this research showed that Perceived Ease of Use variable proved affects towards Perceived Usefulness, Perceived Ease of Use variable unproved affects towards Attitude to Use, Perceived Usefulness variable proved affects towards Attitude to Use, and Attitude to Use proved affects towards Behavioral Intention. The results on the model tested indicates that this model fits to the population.